Eco‐Friendly Spray Deposition of Perovskite Films on Macroscale Textured Surfaces. Issue 2 (15th January 2020) - Sansoni, Simone; De Bastiani, Michele; Aydin, Erkan; Ugur, Esma; Isikgor, Furkan Halis; Al‐Zahrani, Areej; Lamberti, Francesco; Laquai, Frederic; Meneghetti, Moreno; De Wolf, Stefaan
Abstract: An innovative sequential eco‐friendly spray coating (SEF‐SC) technique is developed to uniformly deposit metal halide perovskite films on macroscale textured surfaces, such as textured crystalline‐silicon wafers. Contrasting with previous work on spray‐coated perovskite solar cells, the method presented in this work completely avoids the use of toxic and dangerous solvents. Both MAPbI3 and CsFAMAPbI3− x Br x perovskite films deposited by SEF‐SC show excellent optoelectronic properties and no phase segregation, even when synthesized in ambient conditions. Uniform perovskite coatings are obtained on textured‐silicon heterojunction solar cells underlining the promise of this method, which holds the potential for scalable wet processing of perovskites on rough substrates, such as for low‐cost perovskite/silicon tandem solar cell fabrication. Abstract : An innovative eco‐friendly spray coating technique is developed to deposit metal halide perovskite films on textured surfaces. Uniform halide perovskite films are deposited on textured‐silicon heterojunction solar cells in ambient conditions, showing the potential of this method for scalable wet processing of perovskites on rough substrates, such as for low‐cost perovskite/silicon tandem solar cell fabrication.